Evaluating perceived performance and behavioral intentions of student taking nursing program in CFS, IIUM - Mustaffa, Nooraidah; Fauzi, Muhammad Ashraf; Mat Nawi, Mohd Nazim; Jamaudin, Rosmaya; Ramlan, Nor Siti Hawa; Jemain, Siti Fathimah Putery; Mohd Ali, Noor Sadiah (CFS, IIUM, 2022)
Nursing shortages issue has become primary concern of the hospitals and clinics around the world. Among the initiative of the government is to increase the intake of students to enroll the Nursing (NUS) programme. However, the student’s performance is quite worrying. Performance is always related to competency, which refers to the characteristics that underlie behaviour which describes motives, personality, self-concept, and values of knowledge. Thus, it is essential to have a suitable instrument to measure the perceived performance towards students. This present study was designed to achieve twofold purpose that is to explore on the one hand the relationship between knowledge, skill, attitude, and value (KSAV) and perceived performance, and on the other hand the behavioural intention of for Nursing (NUS) student specifically to complete their study. This study was conducted by Chemistry Department that involved NUS students of Centre for Foundation Studies, International Islamic University Malaysia (CFS, IIUM). Analysis was performed using descriptive analysis and partial least square structural equation modelling (PLS-SEM) based on the KSAV model. Findings revealed that knowledge, skill, attitude and value give significant impact towards perceived performance of NUS student and influenced the behavioural intention of student to complete this program. Additionally, this study is expected to reveal about the learning needs and can contribute to a new measure of designing the curriculum involving Nus student in CFS, IIUM.